Endoscopic Management of Gastrointestinal Leaks and Perforation with Polyglycolic Acid Sheets - Sojung Han; Hyunsoo Chung; Jun Chul Park; Sung Kwan Shin; Sang Kil Lee; Yong Chan Lee (Korean Society of Gastrointestinal Endoscopy, 2017)
Gastrointestinal (GI) leakage, fistulae, and perforations can be serious and life threatening. There has been a paradigm shift in the management approach of these conditions, from surgical to conservative, including endoscopic management. Here, we report two cases of endoscopic closure of a GI fistula and perforation using polyglycolic acid (PGA) sheets with fibrin glue. The first case is of an anastomotic leak detected after subtotal gastrectomy with gastroduodenostomy. After failed application of endoclips, a PGA sheet was applied, and the fistula was successfully closed. The second case was of a 15-mm large perforated gastric ulcer, which was also successfully closed with a PGA sheet. This is the first case report that PGA sheet was used for the treatment of overt perforation. The outcome of these cases suggest that endoscopic closure using PGA sheets can be considered as a useful alternative for the management of GI leakage, fistulae, and perforations.